2007
DOI: 10.1095/biolreprod.106.057828
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′-Monophosphate Kinase-Activated Protein Kinase (PRKA) Activators Delay Meiotic Resumption in Porcine Oocytes1

Abstract: Adenosine monophosphate-activated kinase (PRKA) is a serine/threonine kinase that functions as a metabolic switch in a number of physiological functions. The present study was undertaken to assess the role of this kinase in nuclear maturation of porcine oocytes. RT-PCR and immunoblotting revealed the expression of the PRKAA1 subunit in granulosa cells, cumulus-oocyte complexes (COC), and denuded oocytes (DO). Porcine COC and DO contained transcripts that corresponded to the expected sizes of the designed prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 94 publications
3
48
0
5
Order By: Relevance
“…Increased AMP:ATP ratios indicate a rapid use of intra cellular ATP and is associated with a response to stress. It is likely that AMP-dependent kinases are involved, which have been associated with altered developmental competence cow, mouse and pig oocytes (Richard et al 1997, Downs et al 2002, Downs & Chen 2006, Mayes et al 2007). Furthermore, it was suggested that glycolytic activity was blocked, indicated by the accumulation of fructose bisphosphate and low ATP levels (Ratchford et al 2007).…”
Section: Maternal Environment and Oocyte Developmental Competencementioning
confidence: 99%
“…Increased AMP:ATP ratios indicate a rapid use of intra cellular ATP and is associated with a response to stress. It is likely that AMP-dependent kinases are involved, which have been associated with altered developmental competence cow, mouse and pig oocytes (Richard et al 1997, Downs et al 2002, Downs & Chen 2006, Mayes et al 2007). Furthermore, it was suggested that glycolytic activity was blocked, indicated by the accumulation of fructose bisphosphate and low ATP levels (Ratchford et al 2007).…”
Section: Maternal Environment and Oocyte Developmental Competencementioning
confidence: 99%
“…Accordingly, various analyses have shown that AMPK triggers GVBD in denuded or cumulus-enclosed oocytes of mice (Chen et al 2006, LaRosa & Downs 2006, Chen & Downs 2008. Alternatively, AMPK agonists can block GVBD in other cumulus-enclosed mammalian oocytes (Bilodeau-Goeseels et al 2007, Mayes et al 2007, Tosca et al 2007, although such blockage is apparently due to effects on follicle cells and/or to non-AMPK-mediated pathways (Mayes et al 2007, Tosca et al 2007, Bilodeau-Goeseels et al 2010. However, oocytes of nemertean worms lack follicle cells , and AMPK activations nevertheless inhibit nemertean GVBD (Stricker et al 2010a(Stricker et al , 2010b, indicating that intraoocytic AMPK can stimulate or block MPF activation in different animals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies of intraoocytic AMPK in mice have assessed the relationship between diabetes and AMPK-mediated targets in glucose metabolism (Ratchford et al 2007), the activation of AMPK by FSH and amphiregulin (Chen & Downs 2008), and the interconnections between AMPK and fatty acid oxidative pathways (Downs et al 2009). Moreover, how AMPK interacts with MAPK and other signals has been evaluated in oocytes of cows and pigs (Bilodeau-Goeseels et al 2007, Mayes et al 2007, Tosca et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Dans trois espèces (poule, rate et vache), l'AMPK a été identifiée dans les différents types cellulaires du follicule (ovocyte, cumulus oophorus, cellules de la granulosa et de la thèque) et dans le corps jaune [5][6][7]. Son rôle a été étudié en détail in vitro dans la stéroïdogenèse des cellules de la granulosa [5][6][7] de ces trois espèces et dans la maturation ovocytaire chez la souris, la vache et la truie [8][9][10]. L'AMPK inhibe la sécrétion de la progestérone et/ou celle de l'oestradiol en réponse à l'AICAR ou à la metformine [5][6][7].…”
Section: Lucie Tosca Christine Chabrolle Joëlle Dupontunclassified
“…Quelques études ont par ailleurs établi un lien entre l'AMPK et la maturation méiotique de l'ovocyte [25]. Chez la souris, l'AMPK améliore la reprise de la méiose (accélération du processus de rupture de la membrane nucléaire ou GVBD (germinal vesicle breack down) [8]) alors que chez le porc ou le bovin, une activation pharmacologique de l'AMPK bloque la maturation nucléaire de l'ovocyte (blocage en prophase de première division de méiose ou vésicule germinative (VG) [9,10]). Bien qu'il existe de certaines hormones comme la leptine, l'adiponectine et la résis-tine (trois adipokines), ou encore la ghréline (d'origine gastrique).…”
Section: Steroidogenic Acute Regulatory Protein]) Et Par Une Inhibitiunclassified